2018
DOI: 10.1371/journal.pone.0194521
|View full text |Cite
|
Sign up to set email alerts
|

Shared larval rearing environment, sex, female size and genetic diversity shape Ae. albopictus bacterial microbiota

Abstract: The Asian tiger mosquito Aedes albopictus became of public health concern as it can replicate and transmit viral and filarial pathogens with a strong invasive success over the world. Various strategies have been proposed to reduce mosquito population's vectorial capacity. Among them, symbiotic control of mosquito borne disease offers promising perspectives. Such method is likely to be affected by the dynamics of mosquito-associated symbiotic communities, which might in turn be affected by host genotype and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
(73 reference statements)
1
36
0
Order By: Relevance
“…Many factors including sex, age, size, geographic location, and other physiological status of mosquitoes have been shown to influence mosquito-associated microbiota (Osei-Poku et al, 2012; Zouache et al, 2010; Buck et al, 2016; Minard et al, 2018). Our study corroborated these previous findings and indicated that factors associated with different geographic locations might have impacted microbiota composition variations observed in adult female Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors including sex, age, size, geographic location, and other physiological status of mosquitoes have been shown to influence mosquito-associated microbiota (Osei-Poku et al, 2012; Zouache et al, 2010; Buck et al, 2016; Minard et al, 2018). Our study corroborated these previous findings and indicated that factors associated with different geographic locations might have impacted microbiota composition variations observed in adult female Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a relation between population genetic origin and midgut microbiota was recently shown in two Ae. albopictus populations from tropical (La Réunion) and temperate (Montpellier, Continental France) regions reared under controlled laboratory conditions (Minard et al, 2018). These contrasting data highlight the need to continue investigating the impact of Aedes spp.…”
Section: The Microbiota Of Aedes Mosquitoes: Origin and Compositionmentioning
confidence: 99%
“…), hexadecanoic acid, and stigmast-4-en-3-one has the ability of antimicrobial properties when compared to major components of acetone solvent extracts. According to Minard et al [37], there was an interaction from all the midgut bacterial diversity for Ae. albopictus mosquitoes in their life cycle.…”
Section: Gc-ms Analysis and Identification Of Compoundsmentioning
confidence: 99%